GEOLOGICAL AND STRUCTURAL CHARACTERIZATION OF SOME SHEAR ZONES IN THE QUEBRADAGRANDE COMPLEX NEAR TO MANIZALES AND VILLAMARIA (2016)
The Quebradagrande Complex (Located in the vicinity of Manizales and Villamaria in the Department of Caldas, Colombia) exhibit three zones of low-grade mylonites. These were identified and named, from West to East as: Los Túneles-Río Olivares, El Arroyo-Corinto, and Gallinazo-Río Blanco. An analysis of the deformation mechanisms allow for the identification of areas where these mylonites show foliation with strikes ranging from N/S to NE/SW, and moderate to high angle dips to the SE. In places dip angles are nearly vertical. Likewise, kinematic indicators such as type σ porphyroclast, S-C structures and S-C’ structures allowed to determine displacements right lateral, right lateral-reverse to reverse, with several vergence angles of the stretching lineation to the SW. It is suggested that the system of shear zones is related to the lateral accretion of the Caribbean plate in the Upper Cretaceous.